ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU ROKOK PADA PT. GENTONG GOTRI SEMARANG GUNA MENINGKATKAN EFISIENSI BIAYA PERSEDIAAN - Nova Renta; Handoyo Djoko Waluyo; Sendhang Nurseto (Universitas Diponegoro, 2013)
Raw materials inventory controlling was primarily aimed at achieving cost efficiencies in inventory levels. Inventory cost efficiency will be achieved if the company has done supply controlling of proper raw material. One of the many ways to control the supply of raw materials is to make the purchase in accordance with the production plan and precise calculations to avoid deficiency and excess in the supply of raw materials.Based on the survey results revealed that the purchasing of raw materials using the EOQ total inventory was less than without EOQ. Besides the purchasing with the purchasing frequency EOQ method is smaller than without the EOQ. The purchasing with EOQ method are also safety stock that have been taken into account so that there will be no excess or shortage of raw materials.In making the purchasing of raw materials, PT. gentong gotri Semarang has to use EOQ method in order to save on inventory costs, and hold safety stock to avoid excess or shortage of raw materials.